2019
DOI: 10.1101/616409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution and genetic architecture of disassortative mating at a locus under heterozygote advantage

Abstract: AbstractThe evolution of mate preferences may depend on natural selection acting on the mating cues and on the underlying genetic architecture. While the evolution of assortative mating with respect to locally adapted traits has been well-characterized, the evolution of disassortative mating is poorly characterized. Here we aim at understanding the evolution of disassortative mating for traits under strong balancing selection, by focusing on polymorphic mimicry as an illustrati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Here, our results on the evolution of disassortative mating are obtained assuming a matching rule, and we expect that assuming a preference/trait rule might limit such an evolution, because selection might break the unmatching allelic combinations. In the specific case of polymorphic mimicry, Maisonneuve et al (2019) showed that under preference/trait rule, disassortative mating can emerge only if the preference and the cue loci are fully linked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, our results on the evolution of disassortative mating are obtained assuming a matching rule, and we expect that assuming a preference/trait rule might limit such an evolution, because selection might break the unmatching allelic combinations. In the specific case of polymorphic mimicry, Maisonneuve et al (2019) showed that under preference/trait rule, disassortative mating can emerge only if the preference and the cue loci are fully linked.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations designed from the specific case of Heliconius numata, confirm that heterozygote advantage at the locus controlling color pattern variation may promote the emergence of disassortative mating (Maisonneuve et al, 2019).…”
mentioning
confidence: 87%
“…However the evolution of such mating behavior and its effect on polymorphism remain unclear when selection is locally positive-frequency dependent. Using a mathematical model, Maisonneuve et al [5] clarify the conditions that favor the evolution of disassortative mating in the complicated system of H. numata. In particular, they investigate whether the genetic basis of wing colour can favor the emergence of disassortative mating.…”
mentioning
confidence: 99%
“…And if so, can such evolution lead to the maintenance of local polymorphism in spite of strong positive frequency-dependent selection? To investigate these questions, Maisonneuve et al [5] model evolution at two loci, one is the P locus for wing pattern, and the other influences mating behavior. The population is divided among two connected patches that differ in their butterfly communities, so that different alleles at the P locus are favored by positive frequency-dependent selection in different patches.…”
mentioning
confidence: 99%
See 1 more Smart Citation